Task-Based Language Learning in Action: Improving Writing Skill among Eighth-Grade Students at an Indonesian Islamic School - Annisa Fadlilaturrohmah; Muh Shofiyuddin (International Journal of Research in Education, 2025)
This quantitative study investigates the efficacy of task-based learning in enhancing the English writing skills of second-grade students at Indonesian Islamic School. A total of 70 students were divided into experimental and control classes, with the experimental class receiving task-based learning instruction and the control class receiving traditional teaching methods. Pre-test and post-test assessments were administered to both classes, and student skills were evaluated using a meta-cognitive skills rubric, multiple-choice questions, and essay writing. Data analysis was conducted using descriptive statistics, including normality and homogeneity tests via SPSS and Excel. The results indicate a significant improvement in English writing skills among students in the experimental class (M = 62.43) compared to the control class (M = 60.00). The findings suggest that task-based learning is an effective instructional approach for enhancing students' English writing skills and creativity. The study's results have implications for teaching practices, highlighting the importance of incorporating task-based learning in English language instruction. The findings also suggest that task-based learning can be adapted to various educational settings, providing a valuable tool for educators seeking to improve student outcomes. Furthermore, the study's results contribute to the growing body of research on task-based learning, providing insights into its effectiveness in enhancing language skills. Overall, this study provides evidence for the benefits of task-based learning in English language instruction, and its findings have the potential to inform teaching practices and improve student outcomes.